2001
DOI: 10.1079/bjn2000251
|View full text |Cite
|
Sign up to set email alerts
|

Lower BMI cut-off value to define obesity in Hong Kong Chinese: an analysis based on body fat assessment by bioelectrical impedance

Abstract: There is increasing evidence suggesting that the cut-off values for defining obesity used in the Western countries cannot be readily applied to Asians, who often have smaller body frames than Caucasians. We examined the BMI and body fat (BF) as measured by bioelectrical impedance in 5153 Hong Kong Chinese subjects. We aimed to assess the optimal BMI reflecting obesity as defined by abnormal BF in Hong Kong Chinese. Receiver operating characteristic curve (ROC) analysis was used to assess the optimal BMI predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
118
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 17 publications
7
118
1
Order By: Relevance
“…11 Some studies showed that Asians have lower BMI but higher PBF than Caucasians, and that some Asian population's morbidity and mortality of obesity-related diseases are relatively high at a relatively low BMI level. [12][13][14] From those perspectives, the WHO expert consultation recently reported that the universal BMI criteria for adult obesity are not suitable for Asian populations, although no recommendation for new, clear, BMI cutoff points was given for any Asian population. 15 From this perspective, variations in criteria among various ethnic populations should be considered in evaluating obesity in children.…”
Section: Discussionmentioning
confidence: 99%
“…11 Some studies showed that Asians have lower BMI but higher PBF than Caucasians, and that some Asian population's morbidity and mortality of obesity-related diseases are relatively high at a relatively low BMI level. [12][13][14] From those perspectives, the WHO expert consultation recently reported that the universal BMI criteria for adult obesity are not suitable for Asian populations, although no recommendation for new, clear, BMI cutoff points was given for any Asian population. 15 From this perspective, variations in criteria among various ethnic populations should be considered in evaluating obesity in children.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 5153 Chinese subjects aged 18 -90 y (median age 50.7 y) examining BMI values corresponding to different centiles of body fat (measured by impedance) concluded that overweight should be defined as 23 rather than 25 kg=m 2 , and obesity 26 kg=m 2 rather than 30 kg=m 2 . 12 Thus anthropometric values obtained in this study could serve as indicators for risk of mortality in Usefulness of waist circumference in the elderly J Woo et al Figure 2 Likelihood ratio for mortality at 36 months or to have hypertension or diabetes for various BMI cut-off values. Usefulness of waist circumference in the elderly J Woo et al elderly Chinese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature indicate that the BMI cut-off value for obesity as recommended by WHO (1998) at 30 kg=m 2 for adults could be too high in some Asian population groups (Wang et al, 1994;Gurrici et al, 1998;Deurenberg et al, 1998;Gallagher et al, 2000;Deurenberg-Yap et al, 2000;He et al, 2001;Ko et al, 2001). For example, Indonesians (Guricci et al, 1998), Singaporeans (Deurenberg-Yap et al, 2000) and Hong Kong Chinese (Ko et al, 2001;He et al, 2001) have 5 -7% more body fat percentage compared with Caucasians with the same BMI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Indonesians (Guricci et al, 1998), Singaporeans (Deurenberg-Yap et al, 2000) and Hong Kong Chinese (Ko et al, 2001;He et al, 2001) have 5 -7% more body fat percentage compared with Caucasians with the same BMI. This higher body fat percentage coincides with higher relative risks for cardiovascular risk factors at lower levels of BMI, providing more evidence for the need to lower the BMI cut-off value for obesity in these populations (Ko et al, 1999;Steering Committee, 2000;Deurenberg-Yap et al, 2001).…”
Section: Introductionmentioning
confidence: 99%